Could tumor location-specific lymph node dissection be a tailored approach? - Shimada, Yoshihisa; Ikeda, Norihiko (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
With the advent of personalized medicine, the concept of exploiting patient’s tumor characteristics to make therapeutic decisions has revolutionized the landscape for lung cancer treatment. In the same way, advances in the early detection of small lung cancers by high resolution computed tomography (CT) and subsequent accumulated findings that patients with small peripheral lung cancer with pure or predominantly ground-glass opacities (GGO) in CT images or lower (or negative) 18F-fluorodeoxyglucose-positron emission tomography uptake have favorable outcomes without any lymph node metastasis, have led to incremental change on treatment planning, follow-up methods, and operations towards “individualized surgery” (1,2).